2004
DOI: 10.1177/154405910408300704
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bone Apposition to a Chemically Modified SLA Titanium Surface

Abstract: Increased surface roughness of dental implants has demonstrated greater bone apposition; however, the effect of modifying surface chemistry remains unknown. In the present study, we evaluated bone apposition to a modified sandblasted/acid-etched (modSLA) titanium surface, as compared with a standard SLA surface, during early stages of bone regeneration. Experimental implants were placed in miniature pigs, creating 2 circular bone defects. Test and control implants had the same topography, but differed in surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

88
1,011
10
32

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 1,071 publications
(1,178 citation statements)
references
References 18 publications
88
1,011
10
32
Order By: Relevance
“…Greater bone formation is found around microstructured implant surfaces that have been modified to have high surface energy (modSLA) than around implants with the same topography but with a more hydrophobic surface (SLA) (27). In vitro, osteoblasts are more differentiated when grown on modSLA than on SLA and there is a marked increase in the prostaglandin E 2 (PGE 2 ), TGF-␤1, and OPG content of the conditioned media.…”
mentioning
confidence: 87%
“…Greater bone formation is found around microstructured implant surfaces that have been modified to have high surface energy (modSLA) than around implants with the same topography but with a more hydrophobic surface (SLA) (27). In vitro, osteoblasts are more differentiated when grown on modSLA than on SLA and there is a marked increase in the prostaglandin E 2 (PGE 2 ), TGF-␤1, and OPG content of the conditioned media.…”
mentioning
confidence: 87%
“…It has been shown that the healing procedure can be further improved by additional surface modifications of the implant. For example, bone apposition and soft tissue integration were found to be effectively enhanced when a sand-blasted and acid-etched surface was generated on dental implants [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Innovations in implant material, design, and surface structure improved implant stability and shortened healing periods. 1,2 Following implant placement, especially the initial interaction with proteins and cells is influenced by the implant surface. 3,4 Most implant surface treatments aim at enhancing the activity of bone-forming cells and their mediators to increase new bone formation and promote earlier osseointegration and higher secondary implant stability.…”
Section: Introductionmentioning
confidence: 99%